Russian theatre in the age of High Putinism: politics and aesthetics - Thomas, AJ (2021)
Setting out from the premise that legislation is performative, this study initially explores the relationship between state cultural policy, censorship, and theatre production. The case is made that following the so-called ‘conservative-authoritarian turn’ in Russia in 2012, there has been a gradual return to an interventionist cultural policy qualitatively similar in some respects to that of Soviet-era Socialist Realism. I identify and describe the period in question – which is characterised by intensified censorship in its numerous guises, a new highly prescriptive cultural policy, and arbitrary repressions of nonconformist elements in society – as the period of High Putinism.